Comportamiento de algunas pruebas de ictericia en la fiebre amarilla - Miranda, Guido (1953)
We have had the opportunity to study the laboratory results in 170 patients with the provissional diagnosis of Yellow Fever. From this study we have selected 130 cases, 22 of which died and the clínical diagnosis was confirmed with autopsy and although the rest never had pathological diagnosis, they had the same clinical picture. The following laboratory data was obtained in all of them: direct bilirrubin and total, total cholesterol, total semm proteins and the following floculation tests: cephalin-cholesterol, thymol, coloidal red, coloidal gold and bidesteled water. We might sumarize our findings as follows: 1.-The yellow fever jaundice is characterized by its early appearence in the symptomatic period (third day). It is then rapid and progressive and at its highest between fourth and sixth days, then decreasing slowly and vanishing at the end of the second week. At the highest point of the jaundice the direct bilirrubin was always found to be around 60 per cent of the total. This is the same result that we see in any other hepato-celular jaundice. Those patients who died always showed much higher levels of bilirrubin than those who survived the disease. This difference was so marked and agreed so well with the clinical COluse, that we use this study as an very important factor in determining the prognosis of each particular case. 2.-It was found that those patients who died of yellow fever had shown from the third day of their symptoms a decreased total cholesterol or a very low normal. We do not know when it was iniciated. This finding was manteined or even acentuated in the following days and continue to be so until the critical part of the disease (fifth and sixth days) or until death. In the other hand, we found that patients who survived had a normal total cholesterol during the first part of the disease; during the critical part, their cholesteroI levels were similar to the other gronp. At the time of the convalescence we noted a very rapid increase in their cholesterol leve1s, reaching the originals arouad the fifteenth day. 3.-The total semm proteins of the yellow fever patients showed normal levels in the third day of the disease. Between the third and the fifth days all the patients showed a relative decrease ia their serum proteias. From then oa, those patients who died showed a very marked decrease in their lévels, reaching the lowest in the ninth day. Those patients who survived also showed a decrease in their protein levels; these figures were relatively less marked and their lowest values were found to be around the eleventh day instead of the ninth. During the recovery period the serum protein levels rapidly increased to their normal values. 4.-In general, the so-called floculation tests in the yellow fever patients had a tendency to be negative during the first week of the disease. As the disease progress the floculation tests became positive, but they never reached high levels or specificity. We never found a correlation between the floculation tests and the course of the disease of its prognosis.